Os limites do consenso: o debate sobre a Lei de Anistia de 1979 nos governos democráticos brasileiros (1995-2010) - Juliana Ventura de Souza Fernandes (2013)
This research addresses the debate regarding the Amnesty Law (Law No.6683 of 1979), since the democratic election in 1994. Despite its centrality in the process of transition, the prerogatives over which made the amnesty effective could never forge consensus. The struggle for amnesty, especially from the mid -1970s, assumed an important political and symbolic role at the end of the dictatorship. The issue was appropriated by the project of distention, developed during the governments of Geisel and Figueiredo, which took the lead in the institutional debate on the amnesty making it possible to approve a law whose benefits would extend to militants and military. After the transition, nevertheless, the amnesty continued mobilizing some social groups, hinged around the demands for material and symbolic repair as well as punishment to the torturers. Therefore, our goal was to investigate the framework in which the law was approved, highlighting the historical factors and the politicians who contributed to the consolidation of the reciprocal interpretation. In addition, we sought to understand the context of the rise of the debates around the interpretation of the law, analyzing the role of the main actors involved in the joint that culminated in the formal request for reinterpretation of the amnesty, filed with the Supreme Court by the Brazilian Bar Association in 2008. Based on the analysis of the denial to reinterpret the law, we finally draw some hypotheses about the difficulties, in our current democracy, for the debate on the dictatorial past to gain greater incidence on the public and the political scene.